1985
DOI: 10.1128/mcb.5.5.1009
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal proliferation of Friend murine leukemia virus-transformed myeloblastic cells occurs early in the leukemogenic process.

Abstract: Integrated Friend murine leukemia virus copies were analyzed by the Southern blotting procedure in myeloblastic cell lines obtained after in vitro infection of long-term mouse bone marrow cultures. Several steps leading to the generation of malignant myeloblastic cells after a long latency period were observed in the evolution of infected cultures. Shortly after infection, a random distribution of integrated provirus copies was observed in the DNA of normally differentiating myeloid cells. In contrast, a disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1985
1985
1994
1994

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This observation was surprising because M. dunni cells are known to harbor little endogenous viral information compared with other mouse strains (15). In fact, we observed these bands in all laboratory mouse strains tested so far, including AKV-negative strains and SC1 fibroblasts from wild mice (22). Because this band was not found in DNAs from other species (hamsters, rats, minks, dogs, or humans), it can be concluded that this endogenous F-MuLV-related viral sequence has been conserved along the mouse speciation but remains limited to this species (unpublished data).…”
mentioning
confidence: 77%
“…This observation was surprising because M. dunni cells are known to harbor little endogenous viral information compared with other mouse strains (15). In fact, we observed these bands in all laboratory mouse strains tested so far, including AKV-negative strains and SC1 fibroblasts from wild mice (22). Because this band was not found in DNAs from other species (hamsters, rats, minks, dogs, or humans), it can be concluded that this endogenous F-MuLV-related viral sequence has been conserved along the mouse speciation but remains limited to this species (unpublished data).…”
mentioning
confidence: 77%
“…Their results also indicated that the events leading to malignant transformation resulted in the emergence of one or a small number of tumor cell clones. Sola et al (25) analyzed the integration sites of F-MuLV in myeloblastic cell lines that were transformed by F-MuLV alone and also concluded a monoclonal origin of these cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that the in vitro generation of murine myeloblastic leukemic cells from F-MuLVinfected bone marrow cells is a multistep process (Heard et al, 1984). This process is characterized by the initial proliferation of clonal CSF-dependent cell lines (FDCL) (Sola et al, 1985) which further acquire the capacity of autonomous growth (ACL) and tumorigenicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the in vitro myeloblastic leukemogenic process, the early clonal expansion of factor-dependent cells (Sola et al, 1985) implies a n uncoupling between cell differentiation and proliferation (Sachs, 1980). These cells having lost their differentiation ability still remain under exogenous CSF control for their survival and growth.…”
Section: Discussionmentioning
confidence: 99%